ANALISIS DETERMINAN KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA PERIODE 2014-2023 - Heirunissa (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study aims to analyze the determinants of financial performance (NPF, CAR, BOPO, and FDR on ROA) of Sharia Commercial Banks in Indonesia during the period from 2014 to 2023. The data source used in this research is secondary data in the form of annual financial statements of Sharia Commercial Banks in Indonesia listed on the Indonesia Stock Exchange (IDX) for the period 2014-2023. The data analysis technique used is multiple linear regression with SPSS 26. The classical assumption tests used in this research are the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Meanwhile, hypothesis testing was conducted using the F-test, T-test, and the coefficient of determination. The results of this study indicate that NPF has a negative and significant effect on ROA, CAR has a positive and insignificant effect on ROA, BOPO has a negative and significant as well as dominant effect on ROA, and FDR has a positive and significant effect on ROA. Simultaneous data testing shows that NPF, CAR, BOPO, and FDR have a significant influence and a very strong relationship with ROA in Islamic Commercial Banks in Indonesia for the period 2014-2023. The results of the coefficient of determination calculation show that the influence of NPF, CAR, BOPO, and FDR on ROA is 73.1%, while the remaining 26.9% is influenced by other factors not examined in the model that affect the financial performance of Sharia Commercial Banks in Indonesia for the period 2014-2023.